2019
DOI: 10.1001/jamaneurol.2019.0242
|View full text |Cite|
|
Sign up to set email alerts
|

Fractures and Linear Growth in a Nationwide Cohort of Boys With Duchenne Muscular Dystrophy With and Without Glucocorticoid Treatment

Abstract: Based on studies with relatively small sample size, fragility fractures are commonly reported in glucocorticoid (GC)-treated boys with Duchenne muscular dystrophy (DMD). OBJECTIVE To determine the fracture burden and growth impairment in a large contemporary cohort of boys with DMD in the United Kingdom and in relation to GC regimen. DESIGN, SETTING, AND PARTICIPANTS A retrospective review of fracture morbidity and growth from 832 boys with DMD in the UK NorthStar database (2006-2015), which systematically cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 36 publications
(86 reference statements)
7
55
0
Order By: Relevance
“…Comparison of deflazacort‐treated and prednisone‐treated patients showed reduced COL1A1 levels in deflazacort‐treated patients compared with prednisone treated ones. Interestingly, a recent report shows that treatment with deflazacort was associated with a higher number of vertebral fractures, shorter time to first fracture, and higher linear growth failure . Results of ongoing studies such as the FOR‐DMD study will potentially clarify the effect of these drugs and regimes on bone health and whether events are associated with or predicted by COL1A1 levels in blood.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of deflazacort‐treated and prednisone‐treated patients showed reduced COL1A1 levels in deflazacort‐treated patients compared with prednisone treated ones. Interestingly, a recent report shows that treatment with deflazacort was associated with a higher number of vertebral fractures, shorter time to first fracture, and higher linear growth failure . Results of ongoing studies such as the FOR‐DMD study will potentially clarify the effect of these drugs and regimes on bone health and whether events are associated with or predicted by COL1A1 levels in blood.…”
Section: Discussionmentioning
confidence: 99%
“…VF in children are rare in the absence of traumatic injury (21), and rates vary according to their method of detection. The highest frequencies of VF in secondary osteoporosis occur in boys with GC-treated DMD, where the VF prevalence is >50% (35), and the cumulative incidence is 28% over a median followup of 4 years from GC initiation (36). Children with leukemia, typically on intermittent GC therapy, have a VF prevalence of 16% at the time of diagnosis (3), and a cumulative incidence of 33% up to 6 years following diagnosis (20).…”
Section: Figure 2 |mentioning
confidence: 99%
“…16,17 Notably, a recent study by Joseph and colleagues demonstrated that boys with DMD treated with daily deflazacort had 16-fold increased risk for first fracture. 18 Bisphosphonates are widely used in the treatment of childhood osteoporosis and fragility fractures. 19 Several studies have demonstrated reduced frequency of fragility fractures and improved BMD after bisphosphonate therapy in pediatric patients with osteogenesis imperfecta and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recent study by Joseph and colleagues demonstrated that boys with DMD treated with daily deflazacort had 16-fold increased risk for first fracture. 18 …”
Section: Introductionmentioning
confidence: 99%